Inter-project linkages to create cassava enterprises for expanded markets and utilization - Ntawuruhunga, P.; James, B.; Sanni, L.; Sandifolo, V.S.; Tarawali, G.; Okechukwu, R.; Abass, A. (International Society for Tropical Root Crops, 2012)
The historical view of cassava as “a poor man crop” in Africa has long limited efforts to fully exploit its commercial potential as raw material in the production of food, feed and industrial products. This situation is now changing, led by special projects which promote cassava-based agric businesses for rural development. In mid 1990s, IITA with its partners focused on cassava crop improvement research for development activities within two sub-regional networks EARRNET in East Africa and SARRNET in Southern Africa. A few years prior to and in the wake of the 2008 food price crises, research for development attention focused on multi-country projects using best bet production, processing and marketing approaches, and innovations to ensure sustainable cassava value chains and markets. These included the USAID funded UPoCA and Livelihood projects, CFC funded Cassava Value Chain Projects, BMGF funded GLCI and C: AVA projects. These projects and the special initiatives of some African governments, worth over US$ 80 million, are in line with the NEPAD Comprehensive African Agriculture Development Program (CAADP) which outlines the main agricultural development pillars for Africa and are supported by the NEPAD Pan African Cassava Initiative (NPACI). Whilst the implementation approaches tend to focus on smallholder rural beneficiaries with primary concerns on food security and income generation, private sector participation is slowly being incorporated to underpin sustainable development. Major challenges to overcome include inter-project linkages to facilitate sharing of experiences and lessons to assure complementarities between multi-country, multi-institution and multi-donor projects. This paper, discusses the role of the projects in catalyzing cassava enterprise development in sub-Saharan Africa, identifies options for closer linkages between the different cassava investments and proposes how to mainstream lessons learned into overall development policy and practice of various African institutions and governments.